S. S. Bobrov’s Ode "The Kingdom of Universal Love": Erotogenesis and Phenomenology of Love (1785) - Petrov, Aleksey; Rudakova, Svetlana (Slavica, 2021)
Among the genre concepts of Love formed in the poetry of the 18th century (erotic-political myth about the love of monarchs in an epithalamic ode; triumph of flesh and physiology in priapic ode; hedonism in anacreontic ode) a special place is occupied by the concept of historiosophical ode. In one of the works of this genre – «The Kingdom of Total Love» by S. S. Bobrov – an attempt was made to combine Eros and History. The ideas of Bobrov, a freemason poet, about the origin of Love go back to the myths of various genesis. Another idea was that Love brings light and harmony to non-living nature, and living nature is completely submitted to the Law of Love – the Law of the continuation of Life. In general, Love appears in Bobrov’s historiosophical ode as a harmonizing cosmic force.